Acquisition of English Modal Verbs by Indonesian EFL Learners: A Corpus-Based Analysis of Learning Patterns - Aisyah Aulia Putri; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This corpus-based study explores the acquisition patterns of English modal verbs by Indonesian EFL (English as a Foreign Language) learners through a comprehensive analysis of learner language data. The study utilizes a specialized learner corpus consisting of 2.5 million words drawn from both written and spoken productions of 450 Indonesian learners, covering various proficiency levels. The research focuses on examining the frequency patterns, semantic distributions, and error types associated with modal verb usage across the learner corpus. The study employs a combination of quantitative corpus linguistic methods and qualitative error analysis to uncover developmental trends and persistent difficulties in acquiring English modals. The findings highlight a significant underuse of epistemic modality, which expresses degrees of certainty, and an overreliance on core modals like